2022
DOI: 10.3390/molecules27217587
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Penicillin G Acylase on Vinyl Sulfone-Agarose: An Unexpected Effect of the Ionic Strength on the Performance of the Immobilization Process

Abstract: Penicillin G acylase (PGA) from Escherichia coli was immobilized on vinyl sulfone (VS) agarose. The immobilization of the enzyme failed at all pH values using 50 mM of buffer, while the progressive increase of ionic strength permitted its rapid immobilization under all studied pH values. This suggests that the moderate hydrophobicity of VS groups is enough to transform the VS-agarose in a heterofunctional support, that is, a support bearing hydrophobic features (able to adsorb the proteins) and chemical reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Hence, it could be concluded that the thermal stability of the glycine-treated iβGL was still impaired. On the other hand, blocking the remaining vinyl-sulfone moieties of the divinyl-sulfone-functionalized agarose via incubation in glycine boosted the thermal stability of immobilized lipase (Dos Santos et al 2015 ) and the stability of immobilized penicillin G acylase (Da Rocha et al 2022 ). Moreover, utilizing glycine to block the immobilizer remaining epoxy moieties boosted the thermal stabilities of the ES-105 immobilized transaminase (Jia et al 2020 ) and the Eupergit C iβGL (Torres and Batista-Viera 2012 ) (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it could be concluded that the thermal stability of the glycine-treated iβGL was still impaired. On the other hand, blocking the remaining vinyl-sulfone moieties of the divinyl-sulfone-functionalized agarose via incubation in glycine boosted the thermal stability of immobilized lipase (Dos Santos et al 2015 ) and the stability of immobilized penicillin G acylase (Da Rocha et al 2022 ). Moreover, utilizing glycine to block the immobilizer remaining epoxy moieties boosted the thermal stabilities of the ES-105 immobilized transaminase (Jia et al 2020 ) and the Eupergit C iβGL (Torres and Batista-Viera 2012 ) (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The blocking boosted the thermal stability of the immobilized-blocked enzyme preparation (Dos Santos et al 2015 ). Blocking via incubation in glycine or ethanolamine was also reported to boost the stability of the penicillin G acylase immobilized onto vinyl-sulfone agarose (Da Rocha et al 2022 ). Such stability enhancements were probably consequences of inhibiting the uncontrolled enzyme-immobilizer interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The last paper is on the immobilization of penicillin G acylase [ 23 , 24 ] on vinyl sulfone activated supports [ 25 ]. These supports have been recognized recently as very well suited to yield intense multipoint covalent attachment [ 3 ], and the enzyme had previously immobilized/stabilized on glyoxyl and epoxy supports [ 26 , 27 ].…”
mentioning
confidence: 99%
“…However, the immobilization failed on vinyl sulfone agarose beads. The authors were able to force the enzyme immobilization using high ionic strength and enabling the hydrophobic enzyme adsorption on the moderately hydrophobic support surface, achieving very good stabilization results after optimization of the multi-point covalent immobilization [ 25 ].…”
mentioning
confidence: 99%